Anomaly detection algorithm based on fractal characteristics of large-scale network traffic - XU Xiao-dong1; ZHU Shi-rui2; SUN Ya-min1 (Tongxin xuebao)
Based on the fractal structure of the large-scale network traffic aggregation, anomalies were analyzed qualitatively and quantitatively from perspective of the global and local scaling exponents.Multi-fractal singular spectrum and Lipschitz regularity distribution were used to analyze the fractal parameters of abnormal flow, trying to identify the relationship between the changes of these parameters and the emergence of anomalies.Experimental results show that the emergence of anomalies has obvious signs on the singular spectrum and Lipschitz regularity distribution.Using this feature, a new multi-fractal-based anomaly detection algorithm and a new detection framework were constructed.On the DARPA/Lincoln laboratory intrusion detection evaluation data set 1999, this algorithm’s detection rate is high at low false alarm rate, which is better than EMERALD.